Sound Absorption Coefficients Natural Fibre Reinforced Composites - Elammaran, Jayamani; Sinin, Hamdan (Trans Tech Publications, 2013)
In this Investigation, the influence of two kind of polymers (Urea-formaldehyde and Polypropylene) mixed with natural fibre (Kenaf) were studied for their sound absorption coefficients. Four samples were made; Samples A1 and A2 are made of Kenaf core fibre with adhesive of high emission Urea-formaldehyde resin (HN 100) with 51.6 % solid content. The fabrication of the particle board was done using a hot press for 6 minutes under the pressure of 40 Ton at 1800C for different fibre lengths 1 mm (Sample A1) and 0.6 mm (Sample A2) with weight fraction of 80%. Sample B1 and B2 are made of Kenaf core fibre with polypropylene matrix materials with coupling agent of polyvinyl alcohol. The fabrication of the sample was done using hot press for 30 minutes under the pressure of 1000 Psi at 1800C for different lengths of 1 mm (Sample B1) and 0.6 mm (Sample B2) with weight fraction of 20%. The sound absorption coefficients of samples were measured according to American society for Testing Materials (ASTM E1050 10) two microphone method. It is evident that type of polymer influences the sound absorption coefficients.